Application of magnetic Method on Mapping the Geothermal Sources at Air Putih, Lebong, Bengkulu - Septi edang lestari; Astra Yunita; Riskia Abdul Rahman; Refrizon; Nanang Sugianto (Newton-Maxwell Journal of Physics, 2022)
Measurements have been made using the geomagnetic method in the Air Putih Tourism Area, Tambang Sawah Village, Pinang Belayar District, Lebong Regency with an area of 2000 m x 2500. Data collection was carried out using a Proton Procession Magnetometer (PPM) model G-856, which is a device with a proton sensor. which works based on the precess of the proton nucleus due to changes in the surrounding magnetic field and is equipped with other technical equipment, such as portable GPS (Global positioning system), types of navigation (maps of survey areas), such as talkies, umbrellas, pens, and recorded data. can be observed.. This research serves to map the potenTial for geothermal (geothermal), because this method is one of the geophysical methods that has advanTages in finding geothermal sources.Data processing is carried out using only Microsoft excel which can only plot magnetic anomalies and interpret qualitatively into initial research. To get the total animali, correction of IGRF (International Geomagnetics Reference Field) and correction of Daily Magnetic Value (diurnal). The results of this measurement obtained a magnetic field anomaly graph. This graph shows the high magnetic susceptibility value is found at poinT 43 which is suspected to be an area of economic value rock minerals and is in fracture zones and rocks with low susceptibility values are found at point 29 which can be suspected as a source area. hot water (hydrothermal). Keywords :Geomagnetic, Anomaly, and Hydothermal